Influência de fatores sensoriais e não sensoriais na intenção de compra de suco de uva - Nascimento, Cintia Barros (2018)
Food labeling provides consumers information they want and need to make choices. Several researches have been conducted to verify the conformity labeled packaged foods in Brazil and, in general, the results are mostly unsatisfactory. Juices and nectars are important beverages due to their increasing consumption in Brazil. The most consumed flavor of industrialized juice and nectar in Brazil is the grape juice with 31% of the market. The objective of this work was to verify the influence of sensorial and non-sensorial attributes on the purchase intention of grape juice. To achieve this objective, a physical-chemical and sensorial evaluation of three different grape juice marketed in Brazil was performed using acceptance tests, CATA and RATA; a qualitative and quantitative study was carried out on the conformity of labels of grape drinks marketed in Brazil; a conjoint analysis was carried out considering the following labeling attributes: preservatives, sugar and juice amount. In addition, a market survey was conducted on the consumption of juices in Brazil. Through the market research we can verify that 93.6% of the evaluated ones usually drink juice and that grape juice is one of the most consumed in the country. The price of whole grape juice is one of the impediments to its higher consumption. In the sensory evaluation Juice A (whole juice, glass bottle) was considered less bright, more opaque, with greater intensity of brown color and less intensity of color wine, attributes that justify its lesser intention of purchase. Conjoint analysis results showed that the absece of “100% grape”, “without added sugar” and “without preservatives” information reduces purchase intention. In preference analysis it was found that consumer prefers to buy the package that has most information on the main panel, showing that these information directly influences the purchase intention.